A DEMOCRATIC CONSENSUS? ISAIAH BERLIN, HANNAH ARENDT, AND THE ANTI-TOTALITARIAN FAMILY QUARREL. Issue 48 (7th February 2018) - Hiruta, Kei
Abstract : Amid the ongoing political turmoil, symbolized by the recent violence in Charlottesville, Virginia, books and articles abound today to encourage us to re-read anti-totalitarian classics 'for our times'. But what do we find in this body of work originally written in response to Nazism and Stalinism? Do we find a democratic consensus forged by a shared anti-totalitarian commitment? I doubt it. Considering the cases of Isaiah Berlin and Hannah Arendt, this article highlights discord beneath what may today appear like a post-war democratic consensus. I argue that the anti-totalitarian literature of the last century encompassed multiple political philosophies, which sometimes differed irreconcilably from each other.